REVISITING RAMAYANA: AN ECOFEMINIST ANALYSIS OF SARAH JOSEPH’S THE VIGIL (International Journal of Food and Nutritional Sciences, 2022)
Ecofeminism is identified as a movement that speaks for the environment, women and the marginalised, including queers. It studies how the oppression of women is linked to the oppression of nature. Sarah Joseph is a renowned writer and social activist born in Kerala. She is considered as one of the most prominent women writers in Kerala. She is the founder of Manushi, an organization of thinking women. Her writings focus on women, marginalised as well as the environment. The Vigil is a retelling of Ramayana from the perspective of Angadan. The novel is about the huge ecological destruction caused by Raman’s army, due to the construction of Sethu (bridge), in their mission to rescue Sita. The Vigil is written against the destruction caused by war. The main aim and objective of this study is to analyse and interpret the essence of ecofeminism in The Vigil.